The Role and Regulatory Mechanism of Transcription Factor EB in Health and Diseases - Zhu, Sheng-yu; Yao, Ren-qi; Li, Yu-xuan; Zhao, Peng-yue; Ren, Chao; Du, Xiao-hui; Yao, Yong-ming (Frontiers in Cell and Developmental Biology, 2021)
Transcription factor EB (TFEB) is a member of the microphthalmia-associated transcription factor/transcription factor E (MiTF/TFE) family and critically involved in the maintenance of structural integrity and functional balance of multiple cells. In this review, we described the effects of post-transcriptional modifications, including phosphorylation, acetylation, SUMOylation, and ubiquitination, on the subcellular localization and activation of TFEB. The activated TFEB enters into the nucleus and induces the expressions of targeted genes. We then presented the role of TFEB in the biosynthesis of multiple organelles, completion of lysosome-autophagy pathway, metabolism regulation, immune, and inflammatory responses. This review compiles existing knowledge in the understanding of TFEB regulation and function, covering its essential role in response to cellular stress. We further elaborated the involvement of TFEB dysregulation in the pathophysiological process of various diseases, such as the catabolic hyperactivity in tumors, the accumulation of abnormal aggregates in neurodegenerative diseases, and the aberrant host responses in inflammatory diseases. In this review, multiple drugs have also been introduced, which enable regulating the translocation and activation of TFEB, showing beneficial effects in mitigating various disease models. Therefore, TFEB might serve as a potential therapeutic target for human diseases. The limitation of this review is that the mechanism of TFEB-related human diseases mainly focuses on its association with lysosome and autophagy, which needs deep description of other mechanism in diseases progression after getting more advanced information.